A Study on Students' Perceptions of Digital Sandbox Games for English Vocabulary - Anshory, Syam All; Wulandari, Sri; Asyhar, Wildan Isna (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2025)
This study investigates junior high school students' perceptions of using digital sandbox games to improve their English vocabulary. As traditional rote memorization methods often fail to engage "digital native" learners, this research explores the potential of popular commercial games like Minecraft and Roblox as supplementary educational tools. Guided by theories of second language acquisition (Krashen, 1982; Vygotsky, 1978) and self-determination (Deci & Ryan, 1985), this descriptive study used a quantitative approach with a purposeful sample of 67 students from a specific institution. Data was collected through a Likert-scale questionnaire. The findings reveal that students hold a positive attitude towards game-based learning and perceive these games as effective tools for vocabulary mastery, especially due to their immersive and interactive features. While the games were seen as effective for understanding and remembering new words, students did report challenges, primarily the lack of school support for game- based learning. The results suggest that digital sandbox games can be a valuable, student- centered tool for enhancing vocabulary acquisition, and the study contributes to the limited research on the use of commercial games for formal education among this specific demographic.